Practical Application of Memopoc informatized Memory Test: A test of the procedure - Schade, Nieves; Hernández, Pilar; Elgueta, Bárbara (Revista de Psicología, 2005)
The present study attempted to implement a computerized version of a conventional test. Specifically, through a descriptive statistical model, a pilot application of the test MEMOPOC for evaluating memory was performed in order to determine the applicability of a computerized format. Two aspects where evaluated: the technical and the formal. The sample was constituted by 36 children, from kindergarten to fourth grade elementary, of a municipal school in the district of Concepción. The results indicate that there are few technical errors to correct and also showed the benefits that meant changing to a computerized system. The discussion is based on the projections of the test and benefits of computerized tests in psychometric evaluation.